Increases in Recent HIV Testing Among Men Who Have Sex With Men Coincide With the Centers for Disease Control and Prevention's Expanded Testing Initiative. (28th October 2014) - Cooley, Laura A.; Wejnert, Cyprian; Rose, Charles E.; Paz-Bailey, Gabriela; Taussig, Jennifer; Gern, Robert; Hoyte, Tamika; Salazar, Laura; White, Jianglan; Todd, Jeff; Bautista, Greg; Flynn, Colin; et al.
Abstract: According to National HIV Behavioral Surveillance system data, human immunodeficiency virus (HIV) testing increased among gay, bisexual, and other men who have sex with men from 2008 to 2011 in cities funded by the Centers for Disease Control and Prevention's Expanded Testing Initiative, suggesting that focused HIV testing initiatives might have positive effects.